Group Investigation Technique on Indonesian High School Students’ Writing Skill - Raras Putri Andini; Euis Yanah Mulyana; Arjulayana Arjulayana (Globish: An English-Indonesian Journal for English, Education, and Culture, 2020)
Writing is the work of pouring ideas, expressing those ideas, and organizing them into statements and paragraphs that will be clear to a reader. Five points that students need to pay attention to in writing are content, organization, vocabulary, language use (grammar) and mechanic. Therefore, in this research, the researcher choosed Group Investigation Technique in teaching writing skill. The objective of this research is to discover whether any significant effect or not in the implementation of Group Investigation Technique on Indonesian high school students’ writing skill because the students were not familiar with the written form in English in spite of they have some assignments about that. Some students were not confident to write in English because they were afraid to make mistake in grammar. The researcher used Quantitative approach and Quasi Experiment method with Non–Equivalent Control Group Design. Both of experimental class and controlled class consist of 38 students as the sample of this research. The result of this research is shown the mean score of controlled class (X.FI.1) pretest (58,5) is a little smaller than experimental class (X.FKK.2) pretest (60,26). Meanwhile the mean score of controlled class postest (65,82) is way smaller than experimental class postest (73,4). Based on the data analysis postest of hypotheses testing with significant level 5% (0,05), the result obtained that tcount (3,18) > ttable (1,99) where the statistical hypotheses of H0 was rejected and H1 was accepted. So, it can be concluded that there is significant effect in the implementation of Group Investigation Technique on Indonesian High School Students’ Writing Skill.